2023
DOI: 10.20944/preprints202304.0237.v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cognitive Screening in Older People Using Free-Cog and Mini-Addenbrooke’s Cognitive Examination (MACE)

Abstract: Ageing is the strongest known risk factor for many of the neurodegenerative diseases causing cognitive decline and dementia. Identification of cognitive impairment may be a prelude to appropriate treatment, hopefully disease-modifying. Use of cognitive screening instruments may be an equitable way to identify cognitive impairment. This study examined the use of two such instruments, Free-Cog and Mini-Addenbrooke’s Cognitive Examination (MACE), in patient cohorts referred to a dedicated cognitive diso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…It has been suggested [3,4] that the EI may effectively communicate risk to both clinicians and patients and their families, specifically the risk of correct diagnosis versus misdiagnosis for a particular test, in a way that is more transparent than for sensitivity, specificity, predictive values, and likelihood ratios. The EI values have been calculated for various cognitive screening instruments [3,4,12]. This measure may be of particular value when the administration of invasive tests or tests associated with morbidity and even mortality are being proposed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been suggested [3,4] that the EI may effectively communicate risk to both clinicians and patients and their families, specifically the risk of correct diagnosis versus misdiagnosis for a particular test, in a way that is more transparent than for sensitivity, specificity, predictive values, and likelihood ratios. The EI values have been calculated for various cognitive screening instruments [3,4,12]. This measure may be of particular value when the administration of invasive tests or tests associated with morbidity and even mortality are being proposed.…”
Section: Discussionmentioning
confidence: 99%
“…Balanced and unbiased EI measures were previously introduced to try to take into account the values of P and Q [4]. In these and other studies, the EI values have found application in the assessment of cognitive screening instruments used in the assessment of patients with memory complaints [3,4,12]. The aims of the current paper were twofold: firstly, to extend the EI construct to other formulations, namely "balanced level" and "quality" variants; and secondly, to apply all the described EI variants, both previously described (standard, balanced, unbiased [3,4]) and new (balanced level, quality) to the dataset of a large prospective test accuracy study of a cognitive screening instrument, the Mini-Addenbrooke's Cognitive Examination.…”
Section: Introductionmentioning
confidence: 99%